Effect of Anterior Nasal Packing on Middle Ear Pressure (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Bilateral anterior nasal packing is often done after septal surgery for hemostatic reasons and mechanical splinting. It has been suggested that nasal packing following septal surgery is a frequent cause of short term eustachian tube dysfunction such as ear fullness and mild pain.Objectives: To evaluate the effect of anterior nasal packing on middle ear pressure.Methods: For this prospective, longitudinal study, ninety-two (92) patients admitted for routine septal surgeries were selected according to inclusion and exclusion criteria from the in-patient Department of ENT and Head &Neck Surgery, Dhaka Medical College and Hospital, Dhaka during 1st January 2020 to 31st July 2021. Following informed written consent, the patients were interviewed three times: preoperative, after 24 hours of ANS pack and 6 days after pack removal. During each time, middle ear pressure was measured by an impedance audiometer. Any otological symptoms produced when ANS pack was in place for 24 hours and 6 days after pack removal were also observed and recorded.Results: Among 92 patients in this study, mean preoperative middle ear pressure was -5.5 (± 30.14) daPa. After 24 hours of anterior nasal packing, 70 ears (38%) showed abnormal middle ear pressure among 184 ears. Mean middle ear pressure after 24 hours of ANS pack was -76.5 (± 58.8) daPa. Middle ear pressure again measured after 6 days of removal of ANS pack and showed that the middle ear pressure of all the patients were within normal range. Mean middle ear pressure was -12.4(± 36.5) daPa after 6 days of pack removal. Some otological symptoms developed due to change in middle ear pressure following ANS pack like ear fullness, earache and tinnitus. All these symptoms subsided after 6 days of pack removal.Conclusion: Anterior nasal packing decreases middle ear pressure which is reversible and returns to normal 6 days after pack removal. Some otological symptoms developed due to change in middle ear pressure which were transient and all came to normal after 6 days of pack removal.Bangladesh J Otorhinolaryngol 2022; 28(2): 135-140